2020
DOI: 10.1021/acs.joc.0c00245
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cyclization of o-(1-Hydroxy-2-alkynyl)-N-tosylanilides for the Synthesis of 4-Quinolones

Abstract: The treatment of easily accessible o-(1-hydroxy-2alkynyl)-N-tosylanilides 1 with excess manganese(IV) oxide in the presence of substoichiometric tetrabutylammonium iodide (TBAI) in chloroform (or in the absence of TBAI in dimethylformamide, DMF) promoted a sequential oxidation/intramolecular hydroamination to give 4-quinolones 3 and/or (Z)-2-alkylidene-3-oxindoles (Z)-4 in good yields. Possibly, MnO 2 played dual roles as an oxidant and as a Lewis acidic activator of intermediary ynones 2. The product distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[61] The oxidative processes carried out in the presence of oxygen and visible-light-induced photocatalysis are considered as a green and efficient synthetic strategy to achieve the synthesis of a wide variety of medicinal compounds. Xiaochen et al reported a mild, highly efficient, atom economical onepot synthetic strategy for the synthesis of 4-quinolones (69) . The presence of small electron-withdrawing halogen atom or groups such as methyl led to better yields and high ee (76-86 %).…”
Section: Synthesis Of 4-quinolones Using Visible Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] The oxidative processes carried out in the presence of oxygen and visible-light-induced photocatalysis are considered as a green and efficient synthetic strategy to achieve the synthesis of a wide variety of medicinal compounds. Xiaochen et al reported a mild, highly efficient, atom economical onepot synthetic strategy for the synthesis of 4-quinolones (69) . The presence of small electron-withdrawing halogen atom or groups such as methyl led to better yields and high ee (76-86 %).…”
Section: Synthesis Of 4-quinolones Using Visible Lightmentioning
confidence: 99%
“…The proposed mechanism of the reaction is dissipated below in figure 20. [69] Babu et al, developed a facile, three-component synthesis of 2-amino-3-carboxylate-4-quinolones (101). It was observed that the reaction between phosphorus ylides (97, 1 mmol) and isocyanate (98, 1 mmol) was carried out in 1, 2-DCE at room .…”
Section: Synthesis Of Fused/hybrid 4-quinolone Derivativesmentioning
confidence: 99%